The comparative effects between tocotrieonol-rich fraction (TRF) and α-tocopherol on glutamate toxicity in neuron-astrocyte mono- and co-culture systems - Yap, Hui Min; Khaza'ai, Huzwah; Abd Mutalib, Mohd Sokhini; Musa, Ibrahim (Scholar Science Journals, 2013)
Background: Vitamin E, which can be categorized into tocotrienols and tocopherols, is known to protect cells from glutamate neurotoxicity. Studies have shown that tocotrienol-rich fraction (TRF) protecting the brain against oxidative damage more efficient than α-tocopherol. The role of astrocyte in promoting neuronal survival and recovery after glutamate neurotoxicity is also increasingly appreciated.